Identification of scaling during clean-in-place (CIP) in membrane water treatment process. (December 2019) - Khan, Imtiaz Afzal; Lee, Yong-Soo; Kim, Jong-Oh
Abstract: The goal of this study was to identify the scaling from the chemical cleaning of a polyvinylidene fluoride (PVDF) membrane, fouled by treating a solution containing inorganic foulants (Al, Fe, and Mn) in the presence of kaolin and humic acid as a natural organic matter at Ca +2 strength of 0.5 mMole. Chemical cleaning of the membrane was conducted using solutions prepared in deionized water and permeate water (PW), and the accumulation of insoluble salts on the membrane during cleaning were evaluated. Energy dispersive spectroscopy analysis was used to verify the presence inorganic foulants, and field emission scanning electron microscopy confirmed the changes in membrane symmetry from the accumulation of the foulants. A Fourier-transformed infrared spectroscopy analysis indicated the presence of new functional groups, i.e., C˗Cl and C˗O with bond vibrations at 542 cm −1 and 1, 026 cm −1, respectively, on the membrane surface. The adsorbed mass of HA in the presence of inorganic foulants decreased from 3.54 ± 0.045 mg to 2.24 ± 0.095 mg and 1.71 ± 0.075 mg, and the flux recoveries decreased from 93.2% to 85.69% and 81.92%, for the pristine to chemically DI and PW cleaned membrane, respectively. However, the membrane characterization results confirmed that Al was the major contributor to the accumulation of inorganic salts on the membrane during chemical cleaning and its role was more severe in the presence of Mn. The fitting results of Hermia's fouling models and a specific fouling analysis confirmed the contribution of complete blocking model with increase in irreversible fouling was observed after chemical cleaning. Graphical abstract: Image 1 Highlights: Inorganic foulants adsorbed on membrane in the presence of NOM in water treatment. Inorganic foulants cause scaling during clean in place (CIP) of membrane. Sever scaling produced when CIP solution contains inorganic ions. Al causes more sever scaling problem with trifling role of Mn and Fe.